Global, regional, and national burden of chronic kidney disease, 1990–2017: A systematic analysis for the Global Burden of Disease Study 2017 - GBD Chronic Kidney Disease Collaboration (Lancet, 2022)
This article was published in The Lancet [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access Article under the CC BY 4.0 license..] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)30045-3. The Journal's website is at: https://www.thelancet.com/journals/lancet/article/PIIS0140-6736(20)30045-3/fulltext#%20